O público e o privado na gestão da escola pública brasileira - um estudo sobre o programa “excelência em gestão educacional” da Fundação Itaú Social - BRAGA, Simone Bitencourt (Universidade Federal do Pará, 2013)
This study aims to analyze the implications of the "Excellence in Education Management" of Itaú Social Foundation in managing the Brazilian public school, in terms of theoretical and methodological guide for the documents contained in agreements signed. To that end, we made a documentary research that, through content analysis, attempted to analyze the documents relating to this program. The analyzes showed that the model developed management advocated by Foundation Itaú in Brazilian education is that of the American charter schools, schools financed by the public sector but managed by the private sector. Such schools are presented as having significantly improved educational indicators in the U.S. However, it was found that the reality does not match the one presented by the Program in Management Excellence because the management model based on market parameters, which combines concepts like quality, participation, decentralization, autonomy and evaluation of the idea management resources for the productivity of the education system was not able to improve the American educational system. On the contrary, it has further aggravated the crisis of public education in that country. In Brazil, there have already been experiments in this direction and the analyzes of charter schools that were introduced in Pernambuco revealed that they adopt in their management standards managerial brought from the business world. Therefore, it contains the introduction of market rules from management such as those of goals and results, merit payment for teachers and generalization of evaluation tests, among others. In this context, school autonomy is understood as having increased accountability of teachers and principals for the success or failure of the school, and especially the manager as leader of the whole process. Furthermore, in these schools there are not pedagogical autonomy because the pedagogical project is designed according to productivity criteria previously defined by the responsible program partners (PROCENTRO). The participation that develops in this context is nothing more than a mere process of cooperation, single initiative, adhesion, obedience to the decisions that are taken from top to bottom. Obviously, this management school system does not contribute to the democratization of power relations and cultural formation.